Estimation of Hydrogen Gas Production from Oxidation Process of Zirconium Cladding with Water Vapor in Fukushima Daiichi Nuclear Power Plant Unit One at Japan after Earthquake and Tsunami in 2011 - Endang Lestari; Elin Yusibani; Zulkarnain Jalil; Asril Pramurtadi (PSI-Aceh, 2014)
It has been an explosion at the Fukushima Daiichi NPP caused by the fusion reaction between hydrogen and oxygen. Hydrogen is believed to be generated one of which comes from the oxidation reaction between the fuel cladding and water vapor in the reactor core due to the failure of coolant (LOCA=Loos of Coolant Accident). This study aims to estimate the amount of hydrogen gas that accumulates in the reactor core theoretically by using a model based on equilibrium mole of a chemical reaction. The zirconium cladding material is set as a limiting reagent that limits the formation of hydrogen in the reactor core. The estimation results show that the amount of hydrogen accumulated in the reactor is directly proportional to the mass of the oxidized zirconium with water vapor. The amount of hydrogen that accumulates for one fuel rod reaches 0.018 kg, for one assembly is 1.10 kg and for overall at Unit One reaches 441 kg, which these results have been enough to blow up the reactor.